Kepemimpinan Laki-Laki Terhadap Perempuan Dalam Al-Qur’an: Analisis Penafsiran Zainab Al-Ghazali Dalam Nazharat Fi Kitabillah - Nasution, Aulia Azmi Syahidah; Faza, Abrar M. Dawud (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to examine Zainab al-Ghazali’s interpretation of the concept of qiwāmah in the Qur’an, particularly as articulated in her exegetical work Nazharat fi Kitabillah. Employing a qualitative approach and library research methodology, the study integrates thematic interpretation (tafsir maudhu’i) and character-based interpretation methods. It focuses on how Zainab understands male leadership over women through key verses such as Q.S. an-Nisā’ [4]:34 and Q.S. at-Taubah [9]:71–72, situating qiwāmah within a framework of justice, moral responsibility, and spiritual equality. The findings reveal that Zainab rejects patriarchal readings that legitimize male dominance and instead conceptualizes qiwāmah as a moral trust that demands justice, compassion, and shared responsibility. She emphasizes the Qur'anic notion that believing men and women are guardians of one another, thus affirming moral and spiritual parity despite role distinctions. Her approach, which blends textual fidelity with contextual awareness, provides a bridge between classical interpretations and contemporary Islamic feminist discourse. This study concludes that Zainab al-Ghazali offers a significant contribution to the discourse on women’s tafsir by affirming a Quranic gender model rooted in ethical leadership and communal harmony. Her exegesis demonstrates that gender justice in Islam can be pursued within the bounds of Qur’anic orthodoxy.